THE EFFECT OF THE PROFITABILITY, DEBT POLICY, AND INVESMENT DECISIONS ON FIRM VALUE IN FOOD AND BEVERAGES SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2016-2018 PERIOD - Neli Okta Vera; Rahmawati Rahmawati; Helmiati Helmiati (STIE Bangkinang Publishing, 2021)
Reseach to determine the effect of the effect of Return on Equity , Debt to Equity, and Price Earning Ratio on Price Book Value in food and beverages sub sector companies listed on theindonesia stock exchange (idx) for the 2016-2018 period. Based on the test results simultaneosly and partially, the variable Return on Equity , Debt to Equity, and Price Earning Ratio on Price Book Value ions are proven to have a significant effect on firm value in the food and beverages sub sector companies.The closeness of the relationship between the variabel Return on Equity , Debt to Equity, and Price Earning Ratio on Price Book Value is very strong with the correlation coefficient (R) obtained at 83,5% is influences by other factors not included in this study. Sampling was done using puposive sampling method as 18 samples in the food and beverages sub sector companies. Data analysis performed using multiple linear regression models.